ABOUT THE ORGANIZATION OF TRACK MAINTENANCE AND CONTACT NETWORK FOR FREIGHT-INTENSIVE AREAS - Savenko, O. S.; Muzykina, S. I. (Science and Transport Progress, 2006)
The paper tackles the problem of the time «gaps» in a train schedule. The solution of this complex task needs consideration of the conflicting requirements and working conditions of all the divisions and services of railway transport.